2016
DOI: 10.1089/sur.2014.246
|View full text |Cite
|
Sign up to set email alerts
|

Burden of Surgical Site Infections Associated with Arthroplasty and the Contribution ofStaphylococcus aureus

Abstract: SSIs are associated with increased morbidity, mortality rates, healthcare resource utilization, and costs. Despite the relatively low SSI incidence following orthopedic surgery and specifically arthroplasty, preventive methods, specifically those targeting S. aureus, would serve to minimize costs and improve patient outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 92 publications
1
25
0
Order By: Relevance
“…This is in line with previous observations in Germany, reporting considerable differences in the length of stay between infected and non-infected patients [28,29]. Compared with previous studies in the United States [3,30,31], our hospitalization day results are higher. This reflects differences in the health care practice and reimbursement systems of both states which also account for a longer length of stays in the hospitals in Germany compared to the United States [32].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is in line with previous observations in Germany, reporting considerable differences in the length of stay between infected and non-infected patients [28,29]. Compared with previous studies in the United States [3,30,31], our hospitalization day results are higher. This reflects differences in the health care practice and reimbursement systems of both states which also account for a longer length of stays in the hospitals in Germany compared to the United States [32].…”
Section: Discussionsupporting
confidence: 92%
“…Our results showed overall unadjusted cost ratio within 365 days after index orthopedic surgery of 3.1 among SAI compared with non-SAI patients (p < 0.001). A slightly higher cost ratio (3.7) was seen in patients who underwent knee arthroplasty in a German hospital setting and experience/ did not experience any SSI [29,30].…”
Section: Discussionmentioning
confidence: 91%
“…Across the globe, SSIs are associated with increased morbidity and mortality; sequelae include revision surgeries, poor quality of life, prolonged antibiotic treatment and rehabilitation, and associated lost work and productivity (Control ECfDPa, 2015;Suaya et al, 2014;Tanner et al, 2013;Moore et al, 2015;Gelhorn and Parvizi et al, 2016;Kuhns et al, 2015). Moreover, SSIs are associated with a substantial economic burden to the healthcare system as a result of increased length of hospital stay and increased risk of readmission (Patel et al, 2016(Patel et al, , 2017. Although estimates vary, medical costs have been projected to be between $15 800 and $43 900 per SSI (Kaye et al, 2009;McGirt et al, 2011;Weber et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Costs are even higher for cases of infections caused by methicillin-resistant Staphylococcus aureus (MRSA) as opposed to other pathogens. [5][6][7][8] The last HAI Prevalence Survey, performed in 2011, estimated that about 150.000 SSIs occurred in U.S. acute care hospitals. 9 Accordingly, data of the last Point Prevalence Survey for HAI, promoted by the European Centre for Disease Prevention and Control (ECDC), in 2011-2012, showed that SSIs represent the 20% of HAI (16% in Italy) (http:// ecdc.europa.eu/en/healthtopics/Healthcare-associated_ infections/database/Pages/hai-pps-database-distribution-HAI-types.aspx).…”
Section: Surgical Site Infections (Ssis) Overviewmentioning
confidence: 99%